REFORMULASI PERATURAN TENTANG DISABILITAS DALAM BIDANG PENDIDIKAN BERDASARKAN NILAI KEADILAN SOSIAL - Lestari, Eta Yuni; Diamantina , Amalia; Maskur, Muhammad Azil; Santi, Yeni (LITIGASI, 2024)
Fulfilling the rights of persons with disabilities is a shared responsibility between the government and society. Philosophically and juridically, the legal umbrella is the basis for fulfilling the rights of persons with disabilities in various fields. In reality, there is still discrimination against people with disabilities in various areas of life, including in the field of education. The problem formulation in this paper aims to examine how the reformulation of disability law policy in the education sector is in line with the values ​​of social justice. This research is normative legal research using a conceptual, statutory approach. Sources of legal materials are primary legal materials, namely from legislation, books and journals. The data collection method uses library research, analyzed using a deductive thinking process to draw conclusions. The results of the research show that legal reformulation of persons with disabilities in the education sector is carried out with reference to philosophical (in accordance with Pancasila), juridical (harmonization and synchronization) of regulations regarding persons with disabilities both based on national and global law), and sociological (discrimination against persons with disabilities still occurs). which is contrary to human rights). The reformulation framework proposed by the author, harmonization and synchronization in the use of the term and classification of "disability" in legislation, harmonization and synchronization of rights in the field of education, reviewing inclusive school policies so that they comply with the principles of social justice.